Studies on Neotropical crickets: New species and notes on the classification of Field Crickets genera Anurogryllus and Gryllus (Orthoptera: Gryllidae: Gryllinae) - Cadena-Castañeda, Oscar J.; Díaz, Carlos Julio Arango; López, Víctor Hugo Grande; Cárdenas, Andrea Del Pilar Floréz (Zootaxa, 2021)
In this contribution to the American Field and Short-tail crickets, two new species from the continental and insular area of Colombia are described. Anurogryllus (Urogryllus) edithsantosum n. sp. from the Meta department, is more related to some Caribbean species, and its genital structure fits the morphological current definition of the subgenus Urogryllus, although it has pseudepiphallic median lophi covered with hairs, as it happens in the species of the subgenus Pilosogryllus. The same way, Gryllus (Gryllus) providiensis n. sp. from Providencia Island, San Andres Archipelago is described, this new species has thick hairs on the pronotum as Gryllus (Gryllus) assimilis (widely distributed in America), as well as the color pattern of the cephalic capsule; but the new species is smaller in size, and has a particular organization in the harp veins of the tegmina, which only resembles Gryllus (Gryllus) marchena from the Galapagos Archipelago (Ecuador), from which it differs markedly in its morphology. Finally, the status of the Gryllus species, distributed in Latin America and the Caribbean, is reviewed, and it is recorded which species have acoustic records, and from here we start with the review of this peculiar genus in Latin America.